AN ANALYSIS OF STUDENTS’ FACTORS AND PROBLEMS EFFECTING IN SPEAKING SKILLS - Renaldi, Ikrar Genidal (Borneo Journal of English Language Education, 2020)
This study tries to analyze and find out students' factors and problems that affect students’ ability in speaking skills. The aims of this study are to answer two research questions: (1) what factors and problems affect the students' speaking skills and (2) what factors and problems are most dominant experienced by students which affect their speaking skills. This research uses descriptive qualitative analysis techniques to obtain data. The object of this study was 5th-semester students in the English department, Tidar university. In obtaining data, this study uses a questionnaire used by Marriam (2015) regarding related research. The intention of this study is to find out the students' factors and problems in speaking skills.